Expression pattern and association analysis of porcine matrix metallopeptidase 9 (MMP9) with diarrhea and performance traits in piglets. (April 2020) - Kou, Mingxing; Guo, Dongchun; Liu, Lu; Gao, Xiaowen; Xing, Guiling; Zha, Andong; Shao, Baoshun; Sun, Yuan; Yang, Xiuqin; Wang, Xibiao; Di, Shengwei; Cai, Jiancheng; et al.
Abstract: Matrix metalloproteinase 9 (MMP9) plays critical roles in multiple biological processes, such as reproduction, cell proliferation and differentiation, and host defenses. The aim of this study was to evaluate whether MMP9 is a candidate gene for resistance to diarrhea in piglets. In this study, quantitative real-time PCR was used to analyze the expression of MMP9 mRNA in different tissues of specific pathogen-free piglets. MMP9 was expressed in all the tissues (heart, liver, spleen, lung, kidney, stomach, duodenum, jejunum, ileum, and colon) analyzed. An association analysis between MMP9 polymorphisms and piglet diarrhea score and performance traits were performed in Min (Chinese indigenous breed) and Landrace populations. In the statistical analysis, at the g.48178429 G>A locus, AA piglets had a lower diarrhea score than that of GA in the Min population ( P  < .05), whereas GG had higher day-35 body weight and average daily gain (ADG) than AA in the Landrace breed ( P  < .05). At the rs336583561 locus, Min piglets with the GG genotype have a lower diarrhea score than AG piglets ( P  < .05). At g.48184777C>T, CC animals have higher body weight than TC Landrace piglets ( P  < .05 or P  < .01). A 5′ flanking deletion assay indicated that g.48178429 G>A was not located in the MMP9 promoter region. Our results suggest that the A allele at the g.48178429 G>A locus and the G allele at rs336583561 are resistance alleles in Min pigs. Before these markers are used in pig breeding programs, more studies in larger populations are needed. Highlights: Porcine MMP9 gene was expressed in stomach and gut tissues of SPF piglets. Min piglets carrying the A (g.48178429 G>A) and G (rs 336583561) can increase their capacity to resist the diarrhea.